Hybrid intravascular ultrasound and optical coherence tomography catheter for imaging of coronary atherosclerosis. Issue 3 (4th May 2012) - Li, Brian H.; Leung, Annie S.O.; Soong, Alan; Munding, Chelsea E.; Lee, Hyunggyun; Thind, Amandeep S.; Munce, Nigel R.; Wright, Graham A.; Rowsell, Corwyn H.; Yang, Victor X.D.; Strauss, Bradley H.; Stuart Foster, F.; et al.
<x xml:space="preserve">Abstract</x> Objective To demonstrate the feasibility of imaging human coronary atherosclerosis using a novel hybrid intravascular ultrasound (IVUS) and optical coherence tomography (OCT) imaging catheter. Background IVUS and OCT have synergistic advantages and recent studies involving both modalities suggest the use of a hybrid imaging catheter may offer improved guidance of coronary interventions and plaque characterization. Methods A 1.3 m custom hybrid IVUS‐OCT imaging probe was built within a 4F catheter using a 42 MHz ultrasound transducer and an OCT imaging fiber. Coplanar images were simultaneously acquired ex vivo by both modalities in 31 arterial segments from 11 cadaveric human coronaries. IVUS and OCT images were acquired at 250 μm intervals, of which 13 of the arterial segments were selected as representative of a diverse set of pathological findings. The selected segments were then imaged with either digital X‐ray or micro‐CT, processed for histological analysis and compared with the corresponding IVUS and OCT images. Results Images of human coronary atherosclerosis using the hybrid IVUS‐OCT catheter demonstrated a range of vascular pathologies that were confirmed on histology. The anticipated synergistic advantages of each modality were qualitatively apparent, including the deeper tissue penetration of IVUS and the superior contrast, resolution and near‐field image quality of OCT. Conclusions Preliminary ex vivo images using a hybrid IVUS‐OCT catheter demonstrated feasibility in using the device for intracoronary imaging of atherosclerosis. Future studies will include in vivo imaging and larger samples sizes to enable quantitative comparisons of tissue characterization and feature identification using hybrid imaging catheters versus standalone IVUS and OCT imaging techniques. © 2012 Wiley Periodicals, Inc.